THE EFFECTIVENESS OF MOBILE LEARNING APPS IN PLANT ANATOMY INSTRUCTION - Habibul Akram; Muhammad Yassir; Agus (STMIK Indonesia Banda Aceh, 2024)
This study examines the effectiveness of mobile learning applications in teaching plant anatomy to undergraduate students. As educational technology evolves, mobile apps offer new opportunities for interactive and flexible learning. The research compares student outcomes between two groups: one using a mobile learning app and the other receiving traditional instruction. Using a quasi-experimental method, data were collected through pre-tests, post-tests, and student questionnaires. The findings show that students using mobile apps achieved significantly higher post-test scores and demonstrated better engagement and motivation. The visual and interactive features of the apps helped learners grasp complex anatomical structures more effectively. Despite some technical challenges, such as limited device compatibility, the study concludes that mobile learning apps are a promising tool to enhance plant anatomy instruction. Integration of such tools into the curriculum is recommended to support active and autonomous learning.